Analysis of the data monitored on a ship in operation - Koh, Clarence Jun Xian (Nanyang Technological University, 2022)
The preparation, conduct, and analysis of sea trial have been going through many developments over recent years because of the introduction of the Energy Efficiency Design Index (EEDI). As international standards get more stringent, requirements for a ship's performance prediction accuracy must follow suit. This presents the prospect of developing new correction methods and improving present methods. In-house capabilities to perform sea trial analysis is needed for this purpose. This project aims to develop and validate a Python program that performs Sea Trial Analysis with a selected set of correction methods. This project also aims to create a user interface that collects essential data from the Sea Trial for the program to analyze. The program shows a reasonable degree of accuracy compared to a sample analysis report generated by the publicly available STAIMO software when provided the same inputs. Outputs from the individual correction method faced some degree of deviation. Wind Correction Method produced outliers during intermediate steps but was able to achieve similar values when comparing Final Wind Resistance Correction (RWIND). Wave Correction Method yielded consistent percentage error when comparing to STAIMO. This occurrence was attributed to the different approach to apply of Direct Power Method. The results generated for both Current Correction Method, “Iterative” and “Mean of Means” methods, produced small degree of deviation. It was also observed that the deviation encountered in the final contract evaluation were due to differences in the calculation process between the ITTC 2021 edition and the ITTC 2014 edition. In Chapter 4, it was shown that the Python program was able to reproduce STAIMO's output with an acceptable degree of deviations when following the ITTC 2014 edition.